Learner : preceptor ratios for practice‐based learning across health disciplines: a systematic review. Issue 2 (23rd November 2016) - Loewen, Peter; Legal, Michael; Gamble, Allison; Shah, Kieran; Tkachuk, Stacey; Zed, Peter
Abstract : Context: Practice‐based learning is a cornerstone of developing clinical and professional competence in health disciplines. Practice‐based learning systems have many interacting components, but a key facet is the number of learners per preceptor. Different learner : preceptor ratios may have unique benefits and pose unique challenges for participants. This is the first comprehensive systematic review of the topic. Our research questions were: What are the benefits and challenges of each learner : preceptor ratio in practice‐based learning from the perspectives of the learners, preceptors, patients and stakeholder organisations (i.e. the placing and health care delivery organisations)? Are any ratios superior to others with respect to these characteristics and perspectives? Methods: Qualitative systematic review of published English‐language literature since literature database inception, including multiple health disciplines. Results: Seventy‐three articles were included in this review. Eight learner : preceptor ratio arrangements were identified involving nursing, physiotherapy, occupational therapy, pharmacy, dietetics, speech and language therapy, and medicine. Each arrangement offers unique benefits and challenges from the perspectives of learners, preceptors, programmes and health care delivery organisations. Patient perspectives were absent. Despite important advantages of each ratio for learners, preceptors and organisations, some of which may be profession specific, the 2 : 1 and 2+ : 2+ learner : preceptor ratios appear to be most likely to successfully balance the needs of all stakeholders. Conclusions: Regardless of the learner : preceptor ratio chosen for its expected benefits, our results illuminate challenges that can be anticipated and managed. Patient perspectives should be incorporated into future studies of learner : preceptor ratios.